Digital Engineering Research: A Bibliometric Analysis - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study presents a bibliometric analysis of Digital Engineering (DE), an emerging interdisciplinary field at the intersection of engineering, computer science, and digital technologies. By analyzing data from major academic databases such as Scopus and Web of Science, the study investigates the trends, influential contributors, and key research themes shaping the field. The analysis reveals a significant rise in DE research, particularly in areas like artificial intelligence (AI), machine learning, digital twins, and engineering education. The study identifies major research clusters, including the integration of AI in engineering, the evolving role of digital tools in educational systems, and the increasing focus on sustainability and human engineering. The findings also highlight key contributors and institutions, shedding light on the growing collaboration within the academic and industrial sectors. This paper offers valuable insights into the current state of DE research and suggests areas for future exploration, particularly in human-centered design, sustainable development, and the interdisciplinary application of digital technologies.